(untitled) (Journal of Science and Technology, 2016)
Rock samples in various parts of Ghana have long been known to contain measurable quantities of naturally occurring uranium This study is primarily to measure the alpha-activity in dwellings due to the radiative decay of radon, a progeny of natural uranium. Using the closed can technique., *Of residential dwellings, occupational environment and, soils in Southern Ghana have been calculated from the alpha-track density on CR-39 solid state nuclear track detector. Measurements were made during the three-year period from 1989 to 1992. Such data are important because they are essential for the compilation of reliable information on the population dose to natural lionizing radiation in our country.